DOA NABI INGIN KAYA DAN INGIN MISKIN - Mahfud, Muhammad (UNIVERSUM, 2017)
Prayer is a communication tool of human to the God. One of popular prayer in the community is related to the Prophet’s asking to be a poor man, and in the other side the asking to be a rich man. This article discusses the contradiction of the Prophet’s prayer to be a poor man, and in the other side the prayer to be a rich man through Takhrīj al-Ḥadīth method. The Prophet’s prayers give understanding that the followers should not live with their wealth; however, poor here means simplicity. In other side, the both hadith are ḍa’īf. Keywords: rich, poor, Takhrīj al-Ḥadīth, makna ḥadīth